Psychological predictors, moderators, and mediators of treatment outcome among ART-treated women: a prospective study - Zurlo, Maria Clelia; Vallone, Federica; Cattaneo Della Volta, Maria Francesca (Frontiers in Reproductive Health, 2025)
BackgroundThe value of combining infertility research in the psychological and medical fields, i.e., by exploring psychological factors associated not only with emotional adjustment to infertility experiences but also with treatment outcomes, is well-recognized. However, research that bridges these fields’ boundaries is still narrow, is featured by mixed evidence, and often lacks a valid theoretical framework to comprehensively explore and/or identify the multiple psychological risk and protective factors associated with assisted reproductive technology (ART) treatment outcomes. Thus, there is a need for further research in this promising field of reproductive health to foster a high-quality standard of care for infertile couples.ObjectiveBased on the infertility-related stress model, this prospective study recruited a group of infertile women at the beginning of their infertility treatment (T1) to explore and identify the psychological variables (predictors and moderating and mediating variables) associated with their treatment outcome (Failure/Success) at the 4-year follow-up (T2).MethodsAt the beginning of their infertility treatments (T1, 2019), 120 women completed self-report measures that provided data on their background information (sociodemographic characteristics and type of diagnosis), infertility-related stressors, coping strategies, psychological health (State-Anxiety and depression), and the couple's dyadic adjustment. After 4 years (T2, 2023), medical records were collected to provide data on their treatment outcome (failure or success), duration of infertility, and number of treatment cycles. The main, moderating, and mediating hypotheses were tested using correlational analyses, logistic regression analyses, and Hayes’ PROCESS tool.ResultsThe couple's relationship concern stressor, the adoption of a positive attitude coping strategy, and a perceived couple's dyadic adjustment at T1 were significantly associated with treatment success at T2. Conversely, the social concern stressor, the adoption of an avoidant coping strategy, State-Anxiety, and depression at T1, along with a duration of infertility >3 years and a number of treatment cycles >4 at T2, were significantly associated with treatment failure. Duration of infertility, number of treatment cycles, the couple's dyadic adjustment, and the positive attitude and avoiding coping strategies emerged as significant moderating variables. Depression was a significant mediator in the association between the social concern stressor and the treatment outcome.ConclusionsThis study’s findings provide evidence on the key psychological dimensions that should be assessed and addressed within multidisciplinary counseling interventions to support ART-treated women effectively throughout their infertility path and reduce the risk of treatment failure.